Respostas

2014-05-26T16:54:16-03:00
(x+1)²=0
x²+2x+1=0

a=1   b=2   c=1

Δ=b²-4.a.c
Δ=(2)²-4.1.1
Δ=4-4
Δ=0   ⇒ raiz de 0 é 0

x'=-2+0      -2   
  ¨¨¨¨¨¨¨¨¨¨ = ¨¨¨¨¨¨=- 1
    2.1         2

x"=-2-0       -2  
   ¨¨¨¨¨¨¨¨¨=  ¨¨¨¨¨¨=  -1              S:(-1,-1)
       2.1       2

1 5 1
A melhor resposta!
  • Usuário do Brainly
2014-05-26T17:34:50-03:00
(x + 1)² = 0
(x + 1) . (x + 1) = 0
x² + x + x + 1² = 0
x² + 2x + 1 = 0
Δ = b² - 4 . a . c
Δ = 2² - 4 . 1 . 1
Δ = 4 - 4
Δ = 0

x = (- b ± √Δ)/2 . a
x = (- 2 ± √0)/2 . 1
x = (- 2 ± 0)/2

x' = (- 2 + 0)/2
x' = - 2/2
x' = - 1

x'' = (- 2 - 0)/2
x'' = - 2/2
x'' = - 1
1 5 1